Desenvolvimento de serious game para auxílio ao enfrentamento da obesidade infantil - Dias, Jéssica David (2015)
Educational games and ludic activities can be useful tools and well received by children to achieve the goal of health education. Technology can offer significant benefits to the educational process, and can help to face the childhood obesity, encouraging the learning process and motivating the child to adhere to their treatment. Based on this, it is seen the importance of the insertion of the serious game for the promotion of health. Given the use of technology by children, it is believed in the potential of these resources for changing behaviors in this population, particularly against children obesity. This study aims to develop a serious game to support the fight against the childhood obesity. This is exploratory, not experimental, applied and quantitative research. For the development of the game, the following steps were made: conceptualization, pre-production with development of the Game Design Document (GDD), prototyping, production and the evaluation from specialists. It was developed a prototype in alpha stage. The game was evaluated positively both in terms of gameplay and mechanics, and in relation to the content presented, standing out the game as a powerful strategy for health promotion. The arising information from the evaluation phase held by experts served as subsidy for adjustments to the software to make it available in the future to the target population. It is expected that the design of this serious game encourages greater inclusion of games in health as well as encourage their use in health education. It is also expected that the results of this study provides evidence to support the importance of different strategies for early interventions in the context of childhood obesity.